Data Mining and Internet of Things (IoT) application for Biomedical products - Acuña Acuña, Edwin Gerardo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The evolution of high technology in recent years has allowed the biomedical science sector to improve many of its processes, devices and treatments. With the emergence and reinforcement of artificial intelligence, virtual reality, Big Data and the Internet of Things (IoT), they become allies which are representing a great improvement for these industrial sectors. Process sources may include databases, data warehouses, and other information repositories in the biomedical sciences. Thus, in the current context, the technologies called IoT have become a provider of information and data on a large scale.